Oviposition by a lycaenid butterfly onto old host parts is adaptive to avoid interference by conspecific larvae. - Yukari Mochioka (Public Library of Science (PLoS), 2021)
Oviposition site selection by herbivores can depend not only on the quality of host resources, but also on the risk of predation, parasitism and interference. Females of the lycaenid butterfly Arhopala bazalus (Lepidoptera) lay eggs primarily on old host foliage away from fresh growth, where larval offspring live and feed. Resource availability of young host leaves seems not to affect the oviposition site preference by the females. To clarify the adaptive significance of A. bazalus oviposition behavior on old foliage, we tested three hypotheses: eggs on fresh foliage are (1) easily dropped during rapid leaf expansion (bottom-up hypothesis), (2) more likely to be attacked by egg parasitoids (top-down hypothesis), and (3) frequently displaced or injured by other herbivores (interference hypothesis). In field surveys, rates of egg dropping and parasitism by egg parasitoids were not significantly different between fresh and old host parts. However, the portions of fresh leaves on which A. bazalus eggs had been laid were cut from shoots on which conspecific larvae fed. Laboratory experiments demonstrated that eggs on young leaves were displaced in the presence of conspecific larvae and we observed that fifth instar larvae actively displaced conspecific eggs by feeding on the surrounding leaf tissue. These findings indicate that eggs laid on fresh leaves are at risk of being displaced by conspecific larvae, and support the interference hypothesis. Larval behavior is a likely evolutionary force for A. bazalus to lay eggs apart from larval feeding sites on the host plant.